Reduksi Faktor-Faktor yang Mempengaruhi Kualitas Air Hujan dengan Metode Analisis Komponen Utama - Nitasari, Alfi Nur; Salsabila, Fatiha Nadia; Ramadhanty, Devira Thania; Anggriawan, Muhammad Rizal; Amelia, Dita; Mardianto, M. Fariz Fadillah; Ana, Elly (Universitas Islam Madura, 2023)
The increase in air pollution that occurs due to industrial and economic activities will affect the rainwater content. The vital function of one of the sources of clean, namely rainwater, makes the urgency of research on indications of a decrease in rainwater quality by analyzing the substances contained. The parameters used for the determination of rainwater quality are the degree of acidity, conductivity, calcium, magnesium, sodium, potassium, ammonium, sulfate ions, nitrate ions, chloride ions, total hardness, and acidity. The data source used is data from the Central Statistics Agency (BPS) entitled